Eksistensi tradisi baronde sebagai kearifan lokal di era modernisasi - Ibnu Umar; Irwan Irwan; Hasrul Hasrul; Cici Nur Azizah (Journal of Education, Cultural and Politics, 2026)
The development of modernization has brought significant changes to people's lives and impacted cultural traditions. Many regional traditions have experienced shifts in implementation and even disappeared due to modernization. This study aims to examine the existence of the baronde tradition and the factors that have contributed to its persistence over time. In processing the data, this study employed a qualitative methodology with an ethnographic approach. Data were obtained through observation, interviews, and documentation, involving village officials, traditional leaders, and the local community as informants. The results indicate that the baronde tradition is still practiced by the community, although with some adjustments. This tradition embodies the values ​​of togetherness, mutual cooperation, and an expression of gratitude for God's blessings in agricultural activities. The continuity of the baronde tradition is influenced by the community's cultural experiences, which recognize the benefits of tradition, and also by the cultural understanding passed down through formal and informal education.